Death of Paediatric Surgical Patients in NICU of CMH, Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: The purpose of this study was to explore clinical characteristics and primary surgical diagnosis associated with in-hospital death in pediatric surgical patients admitted to the neonatal intensive care unit (NICU) of Combined Miilitary Hospital (CMH), Dhaka.Aim: To explore the clinical factors associated with in-hospital death in paediatric surgical patients admitted to the NICU over a period of 4 years in CMH Dhaka.Methods: This retrospective study includes all patients admitted to NICU of CMH Dhaka for paediatric surgical diseases between July 2013 and December 2017. Data analyzed to asses factors associated with in-hospital death.Results: A total of 72 cases were included and 61(84.7%) underwent surgery. Fifteen patients (20.8%) died while hospitalized in the NICU. The 5 most common surgical diagnoses were Anorectal Malformation, Intestinal Atresia/ Stenosis, Hirschsprungs disease, Intestinal perforation and meconium related obstruction. Esophageal atresia, necrotizing entero-colitis cases had the highest mortality rate.Conclusion: This study describes EA, NEC, Low birth weight (LBW), prematurity and caesarean delivery associated with significant number of deaths of surgical patients in NICU. Novel approaches for these conditions are required to improve the survival.JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 26-28